Dynamics in the Pursuance of Higher Education’s Mandate Amidst Workload Policy: The Optimism for Academics’ Career Growth - Kaguhangire-Barifaijo, Maria (Advances in Social Sciences Research Journal, 2022)
The paper explores multiple challenges encountered by academics in an attempt to fulfil the mandate of higher education institutions in Uganda of; teaching, research and service to community. Whereas teaching is the core function of any university, research and the third mission had majorly been used to inform most personnel decisions, thereby threatening not only quality but academics’ enthusiasm and growth. Two HEIs; Makerere University and Uganda Management Institute (UMI), were purposively selected to unravel the underlying dynamics using a descriptive design. It was revealed that university teaching was the most gratifying profession, and a cardinal role why universities exist, but research was a prerequisite for exception instructional delivery, evidence based teaching, institutional and individual visibility. Similarly, masterly through research was provided effective service to the community. Nonetheless, as individual academics strive to balance the three roles of teaching, research and service, the policy on minimum workload that majorly focuses on teaching load, has remained a hurdle, thereby jeopardizing academics’ career growth and progression. Paradoxically, even those who have endeavored to publish, suffer not only serious burnout and lack of adequate time to prepare for teaching, but their contract renewals that are constantly in jeopardy due to workload deficits. These stringent benchmarked evaluation tools, have threatened not only individual and institutional profiling, but also, diminished professorial collegiate. Further, it is recommended that institutions review their workload perimeters to take into consideration other aspects such as; number of students one has supervised, program development and review, representation on professional bodies and leadership.